Identifying the ‘Hidden costs’ associated with service offshoring: The implications for customer service through practical application. - Gandhi, Dilesh (2015)
Although there is vast amounts of literature discussing that outsourced offshoring has increased over the last few decades and the benefits that firms can experience from doing so, there now needs to be a research carried out into what effects this strategy has had on the delivery of adequate customer service. This work aims to address the gap in recent literature and highlight the other side of offshoring that organisation often do not consider. We look to identify what is classed as the hidden costs. Offshoring is seen as a particularly sensitive subject to many as they have seen their jobs moved overseas and carried out by someone else at a fraction of the cost. Due to this increasing pressures have been placed on political powers to combat the extent that sending jobs overseas can take. Although presently offshoring only represents a small percentage of business processes, it could rapidly grow and become harmful to the domestic job market.